2015
DOI: 10.1016/j.virol.2015.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinia virus protein A3 is required for the production of normal immature virions and for the encapsidation of the nucleocapsid protein L4

Abstract: Maturation of the vaccinia virion is an intricate process that results in the organization of the viroplasm contained in immature virions into the lateral bodies, core wall and nucleocapsid observed in the mature particles. It is unclear how this organization takes place and studies with mutants are indispensable in understanding this process. By characterizing an inducible mutant in the A3L gene, we revealed that A3, an inner core wall protein, is important for formation of normal immature viruses and also fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…2A). In addition, iF17 produced lower levels of the late structural protein A10, which was also notably not processed to its faster-migrating form, which occurs during virion maturation (81). This is in line with prior reports of late-stage defects in virion maturation in the absence of F17, which involve failed processing of other structural proteins (46,47), and suggests that, although this mutant proceeds through early stages of infection, it subsequently encounters both postreplicative-protein production and virion maturation defects.…”
Section: Resultsmentioning
confidence: 95%
“…2A). In addition, iF17 produced lower levels of the late structural protein A10, which was also notably not processed to its faster-migrating form, which occurs during virion maturation (81). This is in line with prior reports of late-stage defects in virion maturation in the absence of F17, which involve failed processing of other structural proteins (46,47), and suggests that, although this mutant proceeds through early stages of infection, it subsequently encounters both postreplicative-protein production and virion maturation defects.…”
Section: Resultsmentioning
confidence: 95%
“…We speculate that A12 may span the core wall with fragment 3 contacting transcriptosome and p4b interiorly, and fragments 1 and 2 oriented towards the exterior contacting A4, p4a, F17 and TM proteins H3, F9 and H2 (S1 Fig). The compromised VP8 encapsidation upon repression of core wall protein p4b [48] seems consistent with a core wall connection to VP8 also, as does the compromised core wall in absence of VP8 [49]. Since, minimally, ~57 amino acids (aa) of linear beta sheet would be required cross a 20 nm core wall, contacts within A12 of the C-terminal 20% of VP8 and some membrane proteins, appear to be more intimate than a wall’s-width.…”
Section: Resultsmentioning
confidence: 99%
“…The function of A3 has been studied previously using temperature-sensitive mutants where it was found that virions formed at non-permissive temperatures were abnormal in shape, had substantially reduced infectivity, and reached transcription levels less than 2% of the wild-type virus, thus indicating A3 plays a critical role in virion morphogenesis [44]. Additionally, an inducible A3L virus has been generated using lac operon elements in a system where the bacteriophage T7 RNA polymerase is expressed under a late promoter controlled by a lac operator, and the A3L gene is placed under a T7 promoter also controlled by a lac operator [64]. In the presence of inducer (IPTG) the virus formed significantly smaller plaques, and in the absence of inducer, abnormal immature virions accumulated within the cytoplasm and no plaques were observed, demonstrating that A3 is required for normal virion formation.…”
Section: Plos Onementioning
confidence: 99%